Inhibition of human platelet phospholipase A2 activity by unsaturated fatty acids. - Ballou, L R (1985)
Phospholipase A2 (PLA2; phosphatide 2-acylhydrolase, EC 3.1.1.4) activity from human platelets increases significantly when the enzyme is separated from an endogenous inhibitor(s). The inhibitor, associated mainly with a particulate fraction, has now been identified as a mixture of unsaturated fatty acids. Treatment of the inhibitor with trypsin, RNase, DNase, or heat did not diminish its inhibitory activity, which was extractable by organic solvents. Incubation of PLA2 with phospholipids or various neutral lipids, including saturated fatty acids, had little or no effect on enzymatic activity. In contrast, unsaturated fatty acids such as palmitoleic acid (16:1), oleic acid (18:1), linoleic acid (18:2), linolenic acid (18:3), arachidonic acid (20:4), all of which were detected in the particulate fraction, or longer chained unsaturated fatty acids inhibited PLA2 activity by 50% at approximately equal to 5 X 10(-7) M. The level of unsaturated fatty acids in the inhibitor fraction was equivalent to approximately equal to 10(-4) M, apparently sufficient to effectively inhibit PLA2 activity. Methylation of unsaturated fatty acids caused a complete loss of inhibitory activity, and subsequent demethylation restored the activity, suggesting that a free carboxyl group was necessary. Inhibition of PLA2 by unsaturated fatty acids appeared to be noncompetitive. PLA2 absolutely required Ca2+ for activity; the inhibition by unsaturated fatty acids was not reversed by Ca2+. The finding that unsaturated fatty acids are potent inhibitors of PLA2 would explain its generally low activity in human platelet extracts and its marked increase of activity during the course of enzyme purification.